Residual closure of fatigue cracks - Vidler, James; Kotousov, Andrei; Ng, Ching-Tai (International journal of solids and structures, 2024)
The plasticity-induced crack closure phenomenon has been the subject of many previous theoretical and experimental studies. From these studies it was found that in the absence of applied loading, a fatigue crack is likely to be partially closed due to the plastic wake, which is generated behind the tip of a propagating crack. This partial, or residual, closure has many implications for theoretical modelling as well as practical applications. However, no theoretical models have been developed to evaluate what part of a propagating fatigue crack is closed in the free from stress state. Direct 3D FE simulations of the plasticity-induced crack closure are very challenging, time consuming, and are not feasible for a large number of fatigue cycles. Therefore, the current paper utilises a 2D strip-yield idealisation and the distributed dislocation technique to investigate the effects of the stress amplitude and R-ratio of fatigue loading on the residual crack closure. The outcomes of this work may assist in the evaluation of the adequacy and limitations of the current analytical and computational models describing the behaviour of structures containing fatigue cracks, as well as in the interpretation of data from nondestructive defect inspections. [Display omitted] •Evaluation of the closed part of a fatigue crack when free from applied stress.•Analytical strip-yield model solved using the distributed dislocation technique.•Parametric study for a range of parameters of constant amplitude fatigue loading.•Assessment of the adequacy of slit and breathing crack models.